2018
DOI: 10.1371/journal.pone.0199222
|View full text |Cite
|
Sign up to set email alerts
|

Functional levels and MRI patterns of muscle involvement in upper limbs in Duchenne muscular dystrophy

Abstract: The aim of the study was to evaluate the spectrum of upper limb functional activities and imaging finding in a cohort of patients affected by Duchenne muscular dystrophy. Thirty-one patients of age between 5 and 29 years were included in the study (17 ambulant and 14 non-ambulant). They were all assessed using the Performance of Upper Limb (PUL) test and muscle MRI of shoulder, arm and forearm in order to establish if the functional scores obtained at shoulder, mid and distal level related to specific patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…Patients with congenital muscular dystrophy were assessed exclusively by one instrument 47,48 . The other seven instruments were used to evaluate different types of NMDs 9,16,19,27–31,33,36,38–46,49,53–55,58 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with congenital muscular dystrophy were assessed exclusively by one instrument 47,48 . The other seven instruments were used to evaluate different types of NMDs 9,16,19,27–31,33,36,38–46,49,53–55,58 …”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in the USA, 19,27,29,37,41,42,46–48 followed by Italy, 40,45,50,51 Turkey, 28,34,35,39 and the Netherlands 33,36,38,58 . Five studies were multisite and included countries such as France, Spain, Germany, Belgium, Switzerland, Denmark, Canada, Ireland, Australia, Nepal, Peru, and India 9,21,26,52,55 …”
Section: Resultsmentioning
confidence: 99%
“…Our study also found that PUL scale is effective in detecting early upper limb shoulder involvement in DMD patients still in the ambulatory stage with a mean shoulder score of 13.50 (SD 2.33) ( Table 4) followed by a declining trend with age ( Figure 1). In fact, subclinical involvement in latissimus dorsi, serratus anterior, shoulder rotators and deltoid had been detected in patients with full score in shoulder domain by upper limb muscle MRI [29] . Another study with 164 patients with DMD [30] had shown that the onset of shoulder involvement occurred in the ambulatory phase for patients with DMD and the shoulder scoring could range from 2 to 16 (mean 13.98, SD 3.04).…”
Section: Discussionmentioning
confidence: 97%
“…PUL module has the advantage of providing evidence on the functional evolution over time of the disease from distal to proximal levels. After the beginning of this study, a novel version of the PUL module (PUL 2.0) has been validated and shared with the scientific community [13,36,37]. PUL 2.0 is constituted by 22 items, and some items of the previous version were deleted (i.e., items B, I, K, U, and V).…”
Section: Discussionmentioning
confidence: 99%
“…In DMD, the PUL module has been widely studied and used to evaluate changes in the muscular function of upper limbs along with time [36,37]. However, in LGMD and BMD, only Artilhiero studied some patients to investigate the relationship between the PUL module and Jebsen-Taylor Test to assess and monitor upper limb function progression in patients with different MD types [21].…”
Section: Discussionmentioning
confidence: 99%